Monopolistic price setting and supply rigidities in a disequilibrium framework - Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1994)
In the paper, a model of the firm with a delayed adjustment of prices and supply is analyzed. Prices and supply are determined under uncertainty about the location of the demand curve. Three models are distinguished: a price setting with predetermined supply, supply determination with predetermined prices, and a simultaneous price and supply determination. It is shown that many of the results of the deterministic case can be transferred to this stochastic model set-up. The deterministic model is included as a special case of the presented model. However, the model here allows for supply rigidities and labour hoarding and permits the analysis of price adjustment and rationing situations.
Keywords: 330; monopolistic price setting; adjustment delays